Numerical thermal study on CNTs/ C2H6O2– H2O hybrid base nanofluid upon a porous stretching cylinder under impact of magnetic source. (September 2019) - Gholinia, M.; Armin, M.; Ranjbar, A.A.; Ganji, D.D.
Abstract: In this essay, the physical aspects of the steady laminar boundary layer flow of CNTs/(C2 H6 O2 –H2 O) hybrid base nanofluid over a porous stretching cylinder under impact of magnetic force has been explored using 4 th order Runge-kutta (RKF 4) numerical method. The impact of changeable, various parameters like: Reynolds number (Re), CNTs volume fraction (ϕ), Squeeze number (S), and Magnetic parameter (M) on the thermal and flow boundary layers are exemplified quantitatively through figures. As well as, impacts of various nanoparticles are analyzed on the velocity/temperature profiles and Nusselt number. Outputs illustrate that: the parameters S, M and Re have a negative and decreasing effect on skin friction coefficient and Nusselt number, therefore have reduced surface drag force and heat transfer rate. As well as, the choice of types of nanoparticles has a significant impact on the stream function and the cooling/heating processes. Graphical abstract: Image 1